MODEL OF OFFICIAL ACTIVITIES AS A PREDICTOR OF ITS PSYCHOLOGICAL PROVISION (Law and Safety, 2018)
The author has studied the psychological provision of the police officers’ official activities as a technology (a set of forms, methods, techniques, algorithms) for the search, study, creation, preservation, support and restoration of the psychological resource of an individual necessary for the effective implementation.Under the model the author of the article refers to a system of objects or signs, which reproduces some essential properties of the original system; material or ideal system (symbolic, conceptual), which indirectly reflects the system of factors that reproduce, simulate the object at different levels of its organization, self-organization and development. It has been noted that the model approach to the study of psychological aspects of official activities allows to distinguish and analyze, evaluate and correct all the most important psychological phenomena, typical for the solution of official tasks. Official activities, like any other professional activities, are a multi-layered, diverse reality, which can be manifested in different hypostases. Thus, operative and search, combat, guarding, penitentiary, rescue and other activities differ to a large extent in psychological conditions for their implementation. Accordingly, the content of the psychological model of each type of activities will have qualitative specificity.The model allows to create effective systems of psychological provision of professional activity of the police personnel. Its usage provides the opportunity to implement in practice a systematic approach in planning employees’ official activities: to carry out a comprehensive assessment of professional situations, to take into account the relevant state of each element, to influence the object of official activities from different sides, etc. It has been emphasized that without simulating the psychological phenomenology of different types of official activities, it is impossible to create effective systems of its psychological provision.